2019
DOI: 10.3389/fcimb.2019.00280
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Evasion of Chemokine Response Through Suppression of CXCL10

Abstract: Clearance of intracellular pathogens, such as Leishmania ( L .) major , depends on an immune response with well-regulated cytokine signaling. Here we describe a pathogen-mediated mechanism of evading CXCL10, a chemokine with diverse antimicrobial functions, including T cell recruitment. Infection with L. major in a human monocyte cell line induced robust CXCL10 transcription without increasing ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 101 publications
6
41
0
Order By: Relevance
“…Many pathogens evade immune cell recognition by modulating the local chemokine milieu, through local inhibition of chemokine production or the deployment of chemokine-decoys (Antonia et al, 2019;Katzman and Fowell, 2008;Mantovani et al, 2006). Therefore, effector function may be enhanced by a sequential two-step process (Ley, 2014) whereby amplification of the frequency or function of incoming antigen-specific T cells (step 1, exemplified here by inducible PAC-10 niches) is kinetically and spatially separated from the pathogen-infection foci (step 2, movement from activation niches to pathogen foci).…”
Section: Discussionmentioning
confidence: 99%
“…Many pathogens evade immune cell recognition by modulating the local chemokine milieu, through local inhibition of chemokine production or the deployment of chemokine-decoys (Antonia et al, 2019;Katzman and Fowell, 2008;Mantovani et al, 2006). Therefore, effector function may be enhanced by a sequential two-step process (Ley, 2014) whereby amplification of the frequency or function of incoming antigen-specific T cells (step 1, exemplified here by inducible PAC-10 niches) is kinetically and spatially separated from the pathogen-infection foci (step 2, movement from activation niches to pathogen foci).…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified a mechanism of CXCL10 suppression in the context of Leishmania infection mediated by the Leishmania -encoded matrix metalloprotease, GP63 57 . We found that this mechanism of immune evasion is beneficial to the parasite as it inhibits recruitment of anti-parasitic CXCR3 + T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lypophosphoglycan (LPG) and the zinc-metalloprotease GP63: major surface components of Leishmania implicated in the impairment of various macrophage functions, including inhibition of phagolysosomal maturation [69,70], cytokine cleavage [71], and activation of negative regulatory factors [72]. ii.…”
Section: Cutaneous Manifestationsmentioning
confidence: 99%